2015
DOI: 10.15306/mvpjms/2015/v2i2/78308
|View full text |Cite
|
Sign up to set email alerts
|

Study of Various Organisms Associated with Surgical Site Infection and their Sensitivity Pattern

Abstract: Aim: The objectives of this study was to study the various microorganisms causing surgical site infection, to study their antibiotic sensitivity and resistance pattern. Setting: Department of Surgery of a tertiary health care centre with an attached medical college. Material and methods: A total of 89 patients with post operative surgical site infection occurring within 30 days of surgery or 1 year of implant were included as subject material after they satisfy inclusion and exclusion criteria. Results: E.coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…But some studies corroborate our findings. Borse et al, Dessie et al, and Amare et al found E. coli to be the commonest organism (32.58%, 23.1%, and 24.3%, respectively) causing SSI [ 16 - 18 ]. The predominance of GNBs in our study which covered almost two-thirds of the total isolates points towards a difference in organism profile in LMIC compared to high-income countries, especially in resource-scant healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
“…But some studies corroborate our findings. Borse et al, Dessie et al, and Amare et al found E. coli to be the commonest organism (32.58%, 23.1%, and 24.3%, respectively) causing SSI [ 16 - 18 ]. The predominance of GNBs in our study which covered almost two-thirds of the total isolates points towards a difference in organism profile in LMIC compared to high-income countries, especially in resource-scant healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
“…The most common organisms associated are Gram positive organisms like, Staphylococcus and Streptococcus, followed by E.coli, Klebsiella and Pseudomonas. 3 Risk factors responsible for causing SSIs are -age of patient, underlying pre-existing illness stratified based on American Society of Anesthesiologists (ASA) Preoperative Risk Classification, obesity, smoking, other patient factors like trauma, blood transfusions, hypothermia, shock, etc., adequate pre-operative preparation of patient, pre-operative antibiotic prophylaxis, 4,5 intra-operative precautions, and post-operative management.…”
Section: Discussionmentioning
confidence: 99%